Relative activity of hip and knee extensors in sprinting - implications for training - Wiemann, K.; Tiedow, G. (New Studies in Athletics, 1995)
"The objective of this study was to investigate the action of the muscles at the hip and knee joints, with a view to identify those muscles which play a major role in sprinting. Taking, as their hypothesis, that the velocity of a sprinter, running at full speed, is directly related to the velocity of the swing back of the legs - a movement started from the high point of the knee lift down to foot contact and continued during the support phase - the authors use electromyography to trace the possible proportional contribution of the various muscles concerned with extension of the hip and knee joints. They conclude that the muscles mainly responsible for forward propulsion in full speed sprinting are the hamstrings, the glutaeus maximus and the adductor longus. The hamstrings are singled out as the most important contributors to produce highest speed levels."